Calcitriol-enhanced autophagy in gingival epithelium attenuates periodontal inflammation in rats with type 2 diabetes mellitus - Wang, Yanan; Huang, Maoting; Xu, Wanlin; Li, Fulong; Ma, Chunliang; Tang, Xiaolin (Frontiers in Endocrinology, 2023)
Type 2 diabetes mellitus (T2DM)-associated periodontitis is a common disease with high prevalence, associated with persistent infection and complicated manifestations. Calcitriol (1 alpha, 25-dihydroxyvitamin D3, 1,25D) is the active form of vitamin D that plays a protective role in immune regulation, bone metabolism, and inflammatory response. In this study, we constructed a T2DM model in rats by combining a high-fat diet with low-dose streptozotocin. The periodontitis model in rats was developed by ligation and Porphyromonas gingivalis (ATCC 33277) inoculation. Rats were randomly divided into five groups: non-diabetic blank, diabetic blank, diabetes with calcitriol treatment, diabetes with 3-methyladenine (3-MA) treatment, or diabetes with calcitriol and 3-MA treatment. The diabetic rats exhibited an intense inflammatory response and decreased autophagy compared with the non-diabetic rats. Intraperitoneal injection of calcitriol and autophagy inhibitor (3-MA) allowed us to explore the effect of calcitriol on inflammation in the gingival epithelium and the role of autophagy in this process. Treatment with calcitriol resulted in decreased expression of p65 and TNF-α and increased expression of LC3 and Beclin-1. Application of 3-MA significantly suppressed autophagy, which was apparently retrieved by calcitriol. Antibacterial peptide (LL-37) is the only antimicrobial peptide in the cathelicidin family that is found in the human body, and it exhibits a broad spectrum of antibacterial activity and regulates the immune system. The expression tendency of LL-37 was similar to autophagy in this study. The findings indicate that calcitriol-enhanced autophagy positively attenuates periodontitis through upregulation of LL-37 in the gingival epithelium of diabetic rats. Our study provides evidence for the application of calcitriol as an adjunctive treatment for T2DM-associated periodontitis.